Paths of a historiographical metamorphosis. Academic teachings and italian historical-educational research between past and present - Borruso, Francesa (Rivista di Storia dell’Educazione, 2019)
The essay addresses the theme of the epistemological revolution that has taken place in the context of historical-educational studies from the post-war years to the end of the 21st century. In fact, the current structure of the teachings present in Italian universities reflects the long and complex path of epistemological transformation of the historical-educational research that took place between 19th and 20th century - a transformation which not only led to an unprecedented and independent academic configuration of the scientific sector, but also to the delineating of new frontiers of the historical-educational research leading to ever richer results shared with the international scientific community.